Pengaruh Pemberian Terapi Uap Air Dengan Esensial Oil Pegagan ( Centella Astiatica) Terhadap Gangguan Pernafasan Balita Di Klinik Rismala - Umamy, Farida; Puspan Sari, Selvi (Jurnal Masyarakat Indonesia (Jumas), 2023)
Ineffective breathing pattern is a condition where inspiration and/or expiration do not provide adequate ventilation. One effort that can be done is by means of water vapor inhalation therapy. Water vapor inhalation therapy is very helpful in removing obstructions in the respiratory tract. Steam inhalation therapy can be done by adding herbal oils such as Gotu Kola Essential Oil to increase the effects of the treatment. The aim of this study was to analyze the effect of providing steam inhalation therapy with Gotu Kola Essential Oil on ineffective breathing patterns in children. Research Method: This research is a literature review study using 2 articles that were adjusted to the inclusion criteria and analyzed qualitatively. Research Results: Based on the research results of the two articles, it shows that there is an increase in breathing patterns before and a decrease in breathing patterns after being given Gotu Kola Essential Oil steam inhalation therapy and there is an influence of Steam Inhalation Therapy with Gotu Kola Essential Oil on the ineffectiveness of breathing patterns in toddlers. Conclusion: It can be concluded that in both articles the results obtained show the influence of Steam Inhalation Therapy with Eucalyptus Oil on the ineffectiveness of breathing patterns in children. Keywords: Inhalation, Eucalyptus Oil, Breathing Patterns